Laporan Kasus : Pneumotoraks Katamenial pada Wanita 30 Tahun dengan Endometriosis - Maya Nadira Yasmine; Risal Wintoko (Majority, 2020)
Catamenial pneumothorax is a pneumothorax that occurs repeatedly and spontaneously in women, recur within 24 to 72 hours before or after menstrual onset. Catamenial pneumothorax is one of the symptoms of Thoracic Endometriosis Syndrome (TES). This pneumothorax is rare with an incidence of 3-6% in women aged 30-35 years. Pneumothorax occurrences often associated with endometriosis. Pathomechanics of pneumothorax associated with endometriosis is discussed in several literature in four mechanism, that is physiological theory, transition, metastasis-microembolism, and through the diaphragm pathway. The typical clinical cause of pneumothorax is related to menstrual time, usually associated with chest pain that most often occurs (90%), followed by dyspnoea (31%) and cough (rarely). Catamenial pneumothorax in almost all cases occur unilateral on the right side. This case is a 30-year-old woman with a catamenial pneumothorax with endometriosis. The case report explained the relationship between endometriosis and the incidence of catamenial pneumothorax. In this case, clinical characteristic of pneumothorax in patients occurs when entering or in the menstrual cycle, and there is clinical improvement after the management according to catamenial pneumothorax. Therapy given in the case consists of pharmacological therapy to reduce tightness, insertion of water sealed drainage (WSD), and minimally surgical technique namely video-assisted thoracoscopic surgery (VATS).